(untitled) (International Journal of Environmental Sciences, 2025)
India is a nation characterised by a significant proportion of small and marginal farmers who lack the capacity to take advantage of economies of scale. Farmer Producer Organisations (FPOs) have emerged as a possible solution for the many challenges faced by Indian agriculture, bringing a glimmer of positive outlook for the vast number of farmers within the country. The present research was carried out in the state of Mizoram. The data collecting process included the use of the personal interview approach, using a meticulously designed interview schedule, as well as conducting Focus Group Discussions with both member farmers and executives. Data was gathered through a purposeful selection of 16 Farmer Producer Organisations (FPOs) that had been operational for a minimum of 3 years. A random sample of 25 member farmers each was chosen from the selected FPOs using Yamane’s sample size formula. Consequently, a total of 380 farmers were included in the study. The results of the study showed a statistically significant increase (p<0.05) in members’ annual income, number of working days, savings, and landholding size after membership in the Farmer Producer Organisation (FPO). The eta square values of 0.10, 0.18, 0.03, and 0.01 indicated that the magnitude of the intervention on income, working days, saving, and land holding size were negligible.